Perencanaan Slot Parkir (Parkiran Dosen Dan Mahasiswa) Universitas Nuku - Adjam, Idhar (Jurnal Ilmiah Wahana Pendidikan, 2025)
arking facilities are locations designated as parking spaces for motorized vehicles and non-motorized vehicles. Campus parking is an area used to park vehicles within the campus environment. The reason this research was carried out was in order to organize parking activities in an orderly manner. With the designated parking slots, drivers will be expected to park their vehicles neatly in the slots provided. Before determining the size of the parking slot, researchers considered the average size of the vehicle. The distance between parking slots or free space must at least be able to accommodate vehicles of standard size so that the vehicle can be easily parked and reused and does not experience friction with other vehicles when carrying out parking activities. Researchers also consider the type and number of vehicles, which is done so that researchers can determine the number of planned parking slots to anticipate problems with parking capacity. The object of this research is aimed at the parking location, where there are 2 parking locations planned for parking slots, namely planning a parking slot for the student parking lot which is located behind the study room which is specially made for motorbikes and a small parking lot which is located to the right of the lecturer parking lot, planning two parking slots. for cars and two slots also for motorbikes, while the measurement process results were obtained for small parking lots through the measurements we carried out, namely, the overall length of the car park is 750cm consisting of 2 spaces, each space has a length of 375cm. Each space can accommodate 1 parking slot. with a size of 250cm for cars and 1 parking slot measuring 105cm. Free space in planning student parking slots is given on the right and left sides, namely 5 cm each. This greatly influences activities in the parking lot. This free space is provided to provide space in the parking slot area, for parking slots that are narrow or without free space can disrupt the parking process when entering or leaving. In this planning, researchers can conclude that parking activities that do not follow the rules often result in vehicles crowding in the parking lot, and creating parking slots in the parking lot will greatly affect parking flow and parking facilities should be equipped with several items to increase security, such as installing appropriate lighting. appropriate and supervised